Strong Decays of Charm Mesons D*1(2680), D*3(2760), D*2(3000)*Supported by National Natural Science Foundation of China under Grant No. 11375063, and Natural Science Foundation of Hebei Province under Grant No. A2014502017. (1st December 2016) - Wang 王, Zhi-Gang 志刚
Abstract: In this article, we assign the higher charm mesons D*1 (2680), D*3 (2760) and D*2 (3000) to be the 2S 1 −, 1D 3 − and 1F 2 + states, respectively, and study the two-body strong decays to the ground state charm mesons and light pseudoscalar mesons with the heavy meson effective theory. We obtain the ratios among the strong decays, which can be confronted to the experimental data in the future and shed light on the nature of those higher charm mesons.